2012
DOI: 10.1177/000348941212100705
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia in Severe Anorexia Nervosa and Potential Therapeutic Intervention: A Case Series

Abstract: The use of NMES in conjunction with traditional swallowing exercises in the treatment of dysphagia in patients with anorexia nervosa may reduce the need for enteral feeding and prolonged hospitalization. In regard to dysphagia intervention and management within this population and across other populations, rigorous randomized controlled studies are necessary for determining the efficacy of NMES and traditional swallowing therapy implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…In a case‐control prospective study that aimed to evaluate the frequency of esophageal motility abnormalities and related symptoms in a small group of female patients with AN (11 patients with AN‐R, mean age 19.9 years, mean body mass index (BMI) 13.2 kg/m 2 ; 12 patients with AN‐binge/purge (AN‐BP), mean age 25.4, mean BMI 15.5 kg/m 2 ), Benini et al found a relatively low rate of dysphagia with no difference between AN subtypes (3/11 patients with ANR, 1/12 patients with AN‐BP); of note the rate of dysphagia in AN was higher than the rate seen in the matched control group. Patients in the latter study had relatively higher BMIs than those described in the former case series . The small sample sizes in both studies described make it difficult to speculate an overall rate and nature of dysphagia in patients with AN but suggest that targeted therapy helps alleviate symptoms.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…In a case‐control prospective study that aimed to evaluate the frequency of esophageal motility abnormalities and related symptoms in a small group of female patients with AN (11 patients with AN‐R, mean age 19.9 years, mean body mass index (BMI) 13.2 kg/m 2 ; 12 patients with AN‐binge/purge (AN‐BP), mean age 25.4, mean BMI 15.5 kg/m 2 ), Benini et al found a relatively low rate of dysphagia with no difference between AN subtypes (3/11 patients with ANR, 1/12 patients with AN‐BP); of note the rate of dysphagia in AN was higher than the rate seen in the matched control group. Patients in the latter study had relatively higher BMIs than those described in the former case series . The small sample sizes in both studies described make it difficult to speculate an overall rate and nature of dysphagia in patients with AN but suggest that targeted therapy helps alleviate symptoms.…”
Section: Resultsmentioning
confidence: 72%
“…Given the reality that dysphagia impacts a patient's ability to be successfully refeed, it is imperative that the initial clinical assessment include questions pertaining to swallowing and that appropriate investigations be undertaken in cases where difficulties are identified. Oro‐pharyngeal dysphagia symptoms were the presenting symptoms described in a case series of three female patients ages 24–33 years with severe AN [body mass index (BMI) range 9.6–12.7 kg/m 2 ] . During bedside swallowing tests (video‐fluoroscopic swallowing study scales), all the three patients were found to have dysphagia (mild to moderate in two patients; severe in one patient), abnormal oro‐pharyngeal swallowing function, and signs of aspiration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspiration may also occur in AN due to dysphagia that is caused by pharyngeal muscle weakness resulting from protein-calorie malnutrition (Holmes, Gudridge, Gaudiani, & Mehler, 2012). Difficulty swallowing and uncoordinated transfer of the food bolus from the mouth to the stomach may lead to aspiration and then pneumonia.…”
Section: Other Complicationsmentioning
confidence: 99%
“…Numerous case reports on patients with various types of dysphagia also suggest great improvements in swallowing functions [64,65,66,67,68,69]. From the 25 studies [29,32,34,37,38,39,40,41,42,43,44,48,49,51,52,53,54,55,56,57,58,59,60,61,62] identified in this literature search, 18 reported positive results for NMES treatment of dysphagia (table 1).…”
Section: Dysphagiamentioning
confidence: 99%